2017
DOI: 10.17659/01.2017.0036
|View full text |Cite
|
Sign up to set email alerts
|

Primary Ovarian Ectopic Pregnancy

Abstract: Background: Incidence of ovarian ectopic pregnancy is about 0.001% to 0.013% of normal pregnancies. Pregnancy with Copper T device in-situ comes with increased chances of ectopic pregnancy. Case Report: A 23-year lady with intrauterine copper-T device (Cu T 380A) in-situ, presented with complaint of pain in lower abdomen. There was no history of overdue of menstruation. Her urine pregnancy was positive, per vaginum examination showed tenderness and fullness in right fornix, βHCG=4300, ultrasound showed free fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…Another case of primary ovarian ectopic pregnancy with IUD in situ was managed with laparotomy, wedge reconstruction, and repair of the ovary. 14 The defect was limited on the superficial surface which was managed with reconstructive procedures in that case. On the contrary, in our case the defect was deep and fetal tissue invaded the ovary.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Another case of primary ovarian ectopic pregnancy with IUD in situ was managed with laparotomy, wedge reconstruction, and repair of the ovary. 14 The defect was limited on the superficial surface which was managed with reconstructive procedures in that case. On the contrary, in our case the defect was deep and fetal tissue invaded the ovary.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, in most case studies in women with ectopic pregnancy and IUD in situ are invariably ovarian pregnancies. [11][12][13][14]16 With these evidences, it looks necessary to further study the association of IUD and ovarian pregnancy and thus highlight the concept of "IUD Associated Ovarian Pregnancy Phenomenon." The idea is, IUD leads to mild inflammation of the uterus and nearby fallopian tube and also may lead to obstruction in ovum conveyance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient in our study was tachycardic and ultrasonography revealed features of gross collection intraperitoneally and was managed with laparotomy. Another case of primary ovarian ectopic pregnancy with IUD in situ was managed with laparotomy, wedge reconstruction and repair of the ovary [12]. The defect was limited on the superficial surface which was managed with reconstructive procedures in that case.…”
Section: Discussionmentioning
confidence: 99%
“…Most case studies in women with ectopic pregnancy and IUD in situ are invariably ovarian pregnancy [9][10][11][12]14]. With these evidences, it looks necessary to further study the association of IUD and Ovarian pregnancy and thus highlight the concept of 'IUD Associated Ovarian Pregnancy Phenomenon'.…”
Section: Discussionmentioning
confidence: 99%